Manajemen Keuangan Madrasah dalam Pengadaan Sarana dan Prasarana Pendidikan - Senang Senang; Erik Rikza Aulia; Sunardi Sunardi (At Tadbir: Islamic Education Management Journal, 2024)
This study underscores the importance of effective financial management in the procurement of educational facilities and infrastructure at MA Al Washoya Ngoro Jombang, aiming to support optimal learning processes. Effective financial management is essential to ensure that the madrasah can provide adequate facilities in line with established educational standards. The objective of this research is to analyze how financial management is implemented at MA Al Washoya, focusing on planning, inventory, and evaluation related to the procurement of educational facilities and infrastructure.The research employs a qualitative descriptive approach, using data collection techniques such as observation, interviews, and documentation. The study examines the financial planning process involving the Waka Sarpras, fund allocation based on annual work meetings, and how inventory and financial evaluation are conducted to ensure proper and efficient use of funds.The findings reveal that financial management at MA Al Washoya is functioning reasonably well; however, there are areas requiring improvement, particularly in optimizing procurement and maintenance of existing facilities and infrastructure. The evaluation indicates that, although facilities and infrastructure have been planned and procured, better maintenance is needed to ensure their sustainability. The study recommends that the madrasah be more proactive in financial planning and asset maintenance strategies to ensure the achievement of high-quality and sustainable educational outcomes.